Making a case for the domestication of CEDAW in Nigeria: empirically and conceptually justified - Olatokun, Ganiat Mobolaji (IISTE, 2014)
Despite the laudable provisions of the Convention on the Elimination of all forms of Discrimination Against Women, (CEDAW), aiming to stop discrimination against women, the widely spread abortion right interpretation given to the provisions of reproductive right under Article 16(e) of CEDAW has made it impossible for Nigeria, a country with a restrictive abortion law to domesticate CEDAW.The authors here, have deviated from the general interpretation, and have consequently made a case for the domestication of CEDAW in Nigeria, using reproductive right, under a progressive interpretation, as the basis. Under a progressive interpretation of CEDAW’s reproductive rights, Primary Health Care (PHC) will serve as an embedded principle, whereby the right to health for women will be the determining factor. Also, the authors have strengthened their case by conducting a case study in eight (8) different states in Nigeria. This step, according to the authors, will serve as a basis for future policy development in the area of reproductive right in Nigeria.